Structure and Specific Characteristics of Economic Culture in Historical Development (Eurasian Scientific Herald, 2023)
The article is devoted to the issues of revealing modern development trends of sociophilosophical theory. It describes the tasks of modern philosophical thinking, new methodological aspects of researching social events and phenomena, and the foundations of the existence of social reality. The article also explores the relationship between religion and science, the relationship between religion and the secular state in the dialectical relationship between religion and society